Is prehospital lactate testing useful in improving clinical assessment?. (2nd June 2019) - Robinson, Simon
Abstract : Introduction: Lactate devices offer the potential for paramedics to improve patient triage and escalation of care for specific presentations. There is also scope to improve existing prehospital tools by including lactate measurement. Method: A literature search was conducted using the Medline, CINAHL, Academic Search Premier, Sciencedirect and Scopus databases. Findings: Acquiring prehospital lactate measurement in trauma settings improved triage and recognition of the need for critical care. Within a medical setting, studies offered mixed results in relating prehospital lactate measurement to diagnosis, escalating treatments and mortality. The accuracy of prehospital lactate measurements acquired varies, which could impact decision making. Conclusion: Prehospital lactate thresholds could aid decision making, although the literature is limited and evidence varies. Lactate values of ≥4 mmol/litre in medical and ≥2.5 mmol/litre in trauma patients could signify that care should be escalated to an appropriate facility, and that resuscitative measures should be initiated, particularly with sepsis, as reflected by standardised lactate values that guide treatment in hospitals. Similarly, a lactate value of <2 mmol/litre could mean de-escalating care into the community, although further research is warranted on this.